Broadway musicals show by show - Green, Stanley (Guilford, Connecticut Applause Theatre & Cinema Books, 2019)
This updated edition of one of the bestselling and comprehensive Broadway reference books, first published in 1985, has been expanded to include many of the most important and memorable productions of American musical theater, including revivals. Arranged chronologically, beginning with musicals from just after the Civil War, each successive edition of the book has added valuable updates about trends in musical theater as well as capsule features on the most significant musicals of the day. The ninth edition documents important musicals produced since the end of the 2012-2013 season through spring 2019.
Keywords: Musicals -- New York (State) -- New York -- History and criticism